The effect from different level of Melinjo (Gnetum gnemon Linn) leaf extract and storage duration on the quality of duck eggs. Issue 1 (April 2020) - Mukhlisah, A N; Abustam, E; Maruddin, F
Abstract: Eggs are one of perishable food products and a very short shelf life. If the eggs are left in the opened air (room temperature), it is lasting only for about 10-14 days. After these days, the eggs undergo alteration of the damage such as evaporation of water content, foul smelling and changing taste. Efforts to overcome the damage, it is necessary to perform preservation. Preservation can be done by marinating. Marinating eggs can be conducted by soaking with various solutions such as lime water or vegetable tanners containing tannins. Melinjo leaves contain high levels of tannins 4.55% which are expected to be one of the vegetable tanning materials. The experiment was conducted in the Laboratory of Animal Technology. This study was used 176 duck eggs that were arranged using completely randomized design (CRD) of factorial pattern 4 x 4 with 3 replications, and consisting of 2 factors. The first factor was the levels of melinjo extract ( 0%, 30%, 40% and 50% ) and the second factor was storage duration (1, 14, 21 and 28 days, respectively ). The results of this study showed that higher levels of leaf melinjo extract, the Haugh unit (HU) value was increased and the depth of the air cavity was decreased. The longer of the storage duration, the lower of HU value of yolk index. On the other hand, the depth of air cavity, depreciation, were increased. In brief, Melinjo leaf extract (30%) can be used as a preservative of duck eggs.